Activated Charcoal for Pesticide Inactivation - Frederick M. Fishel (EDIS)
Revised! PI-164, a 4-page fact sheet by F.M. Fishel, describes what activated charcoal is, how it is used for spill remediation and inactivating pesticides, how to apply it, and how to determine the amount to use. Includes references. Published by the UF Department of Agronomy, June 2008.